2003
DOI: 10.1007/s005350300065
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the pancreatic secretory trypsin inhibitor gene in familial and juvenile pancreatitis in Japan

Abstract: The same set of N34S mutations (N34S + IVS1-37T>C + IVS3-69insTTTT) that exists in other countries was found in the PSTI gene in Japanese familial and juvenile pancreatitis patients. Another unique mutation (R67C) was also observed in two patients; 272C>T was suggested to be a normal polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 19 publications
3
21
2
Order By: Relevance
“…As previously reported [7,9,12] , N34S mutation cosegregated with IVS1-37T 1 C. In addition, the -215G 1 A mutation was in a complete linkage with IVS3 + 2T 1 C (D´ = 1). The [N34S; IVS1-37T 1 C] mutation was found in 8 of 80 patients with CP and in 1 patient with SLE-related AP.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…As previously reported [7,9,12] , N34S mutation cosegregated with IVS1-37T 1 C. In addition, the -215G 1 A mutation was in a complete linkage with IVS3 + 2T 1 C (D´ = 1). The [N34S; IVS1-37T 1 C] mutation was found in 8 of 80 patients with CP and in 1 patient with SLE-related AP.…”
Section: Resultssupporting
confidence: 55%
“…SPINK1 is thought to be the fi rst line of defense against prematurely activated trypsinogen [16] , and the loss of SPINK1 function results in the increased intrapancreatic trypsin activity [7,8] . Although it is still controversial, it has been suggested that mutations in the SPINK1 gene are associated with a predisposition to pancreatitis [7][8][9][10][11][12] . We here showed that two SPINK1 mutations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 By contrast, all four remaining missense mutations (ie p.D50E, 26 p.Y54H, 27 p.R65Q, 28 and p.R67C 29,30 ) were found in isolated patients or families. Of the six variations, only p.N34S and p.R67C were subjected to functional characterization, whereas the former one was shown to be fully active, 20 the latter was suggested to significantly affect PSTI's conformation.…”
Section: Resultsmentioning
confidence: 89%
“…Although these mutations may affect the conformation of nearby active sites, there has been no evidence that this mutation affects the binding affinity and inhibitory activity of SPINK1 to trypsin [27,29]. Interestingly, N34S, the most commonly observed mutation, was shown to cosegregate with two intronic mutations: IVS1-37T>C and IVS3-69insTTTT [6,28,57,75]. This suggests that these intronic mutations, rather than N34S itself, are associated with the predisposition to pancreatitis.…”
Section: Spink1/spink3 As a Trypsin Inhibitormentioning
confidence: 87%
“…There have been many reports on the association between mutations in the SPINK1 genes and patients with pancreatitis [7,24,28,30,55,75]. Although these mutations may affect the conformation of nearby active sites, there has been no evidence that this mutation affects the binding affinity and inhibitory activity of SPINK1 to trypsin [27,29].…”
Section: Spink1/spink3 As a Trypsin Inhibitormentioning
confidence: 99%